PH‐Responsive Charge‐Convertible N‐Succinyl Chitosan‐Quercetin Coordination Polymer Nanoparticles for Effective NIR Photothermal Cancer Therapy. Issue 19 (15th August 2022) - Bhartiya, Prabha; Chawla, Ruchi; Dutta, Pradip K.
Abstract: In recent years, a combination of photothermal therapy (PTT) with chemotherapy has emerged as a new promising strategy to achieve synergistic cancer therapeutic efficacy. Coordination polymer nanocomposites (CPNs) are a new generation of photothermal agents (PTAs) for cancer therapy owing to their high photothermal transduction efficiency, excellent biocompatibility as well as biodegradability and bioactivity. In this study, a robust and scalable synthesis of pH‐sensitive charge convertible NSC‐Fe‐Que coordination polymer nanoparticles (CPNs) based on the coordination reaction between Fe 3+, anti‐cancer prodrug quercetin (Que), and pH‐sensitive zwitterionic biopolymer N ‐succinyl chitosan (NSC) is reported. The as‐prepared CPNs exhibit slightly negative zeta potential at neutral pH while positive zeta potential at pH 6.5, which ensures long blood circulation and high accumulation in the tumor region. NSC‐Fe‐Que CPNs exhibited strong absorption in NIR (500–850 nm) region and displayed a good anticancer effect against A549 cells attributing to the chemo‐photothermal synergistic effect. This study demonstrated that the NSC‐Fe‐Que CPNs hold great promise as an effective thermo‐chemotherapy agent for combination therapy against cancer. Abstract : Based on the coordination reaction between Fe 3+, anti‐cancer prodrug quercetin (Que), and pH‐sensitive zwitterionic biopolymer N ‐succinyl chitosan (NSC), a robust and scalable synthesis of pH‐sensitive charge convertible NSC‐Fe‐Que coordination polymer nanoparticles (CPNs) is reported. These CPNs exhibited strong absorption in NIR (500–850 nm) region and displayed a good anticancer effect against A549 cells attributing to the chemo‐photothermal synergistic effect.